Itraconazole in the therapy of candidosis of uro-genital system and/or oral cavity and throat mucosa in a daily dose of 100 mg - Urbanowski, S... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
The results of a clinical study on the effectiveness and tolerability of itraconazole used in oral therapy of candidosis in a single dose of 100 mg daily were presented. Investigations were performed in 3 groups: 20 persons with candidosis of the urogenital system, 18 persons with candidosis of the oral cavity and throat mucosa. All strains of yeast-like fungi isolated from patients were susceptible to itraconazole. The values of MIC were from 0,01 to20,0 ug/ml. In three groups of patients results and duration of treatment were: 1st group - 90%, from 4 to 8 days; 2nd group - 88,9%, from 4 days to 10 weeks; 3rd group - 90%, from 4 days to 12 weeks. Two weeks after the end of the therapy the recurrence of the disease was observed in 4 persons (8,3%). In2 patients (4,2%), transient adverse reactions - neusea and stomach ache were observed. No changes in laboratory tests (Aspat, Alat, bilirubin) were noticed. It was concluded that itraconazole applied in a single dose of 100 mgdaily is effective and safe. In the authors' opinion therapy should be continued until negative results of clinical and mycological studies of all morbid yeast foci.
Keywords: Administration and dosage; Candidiasis, oral; Candidiasis, vulvovaginal; Drug therapy; Follow-up studies; Itraconazole; Therapeutic use; Treatment outcome